Sistem Pakar Menggunakan Metode Certainty Factor dalam Akurasi Identifikasi Penyakit Panleukopenia pada Kucing - Dyan Mardinata Putra; Gunadi Widi Nurcahyo (Rektorat Universitas Putra Indonesia YPTK Padang, 2020)
Feline Panleukopenia is a disorder caused by inflammation of Feline Parvovirus. This viral inflammation can trigger inflammation of the digestive system in cats and can also attack the cat's bone marrow, and the total white blood cells in the cat's body will decrease. At this time, many people do not know how to accurately identify the disease Feline Panleukopenia in cats and as a result of that cats who suffer from it experience illness and even death. This study aims to determine the level of accuracy in identifying Panleukopenia in cats. There are several types of symptoms that refer to Feline Panleukopenia. Furthermore, the data is processed manually with the Certainty Factor method and continued by using a website-based expert system software. The processing stages are rule solving, determining the weight value of each symptom and calculating the Certainty Factor value with the rule formula. The results of the data processing are continued with the calculation of the level of accuracy. The result of testing this method is that there are 100% of the 5 test data. Based on the accuracy of the identification results of this system, this study is very precise in the level of identifying the level of accuracy of feline panleukopenia. Expert testing systems have been able to specifically identify Feline Panleukopenia. Through the Certainty Factor method, the level of accuracy that can be obtained is quite accurate and can help veterinarians improve their accuracy to identify Feline Panleukopenia in cats.